(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the phenomenon of ignorance as a complex object of philosophical and social research based on a comprehensive approach. Ignorance is interpreted not merely as a lack of knowledge, but as a condition associated with the decline of cognitive activity, the weakening of conscious and critical perception of reality, and the inability to adequately comprehend social processes. Within the framework of the history of philosophy, various theoretical approaches to ignorance are analyzed, and the views of Eastern and Western thinkers are comparatively examined. Particular attention is paid to the social content of ignorance, including its impact on social development, the level of social consciousness, the spiritual environment, and social stability. In the context of contemporary social reality, new forms of ignorance are identified and scientifically substantiated, such as the uncritical perception of information, lack of legal and political knowledge, and spiritual indifference. The research findings demonstrate that enlightenment, education, and philosophical thinking play a decisive role in overcoming ignorance